Pengelolaan Keaslian Rasa dan Budaya pada Restoran Etnik Khas Jawa: Analisis Atmospheric Restoran Etnik Khas Jawa di Jakarta Selatan dan Jakarta Pusat - Widyakusumastuti, Maria Anggia (Humaniora, 2014)
This research performed the authenticity of Javanese ethnic flavor and culture in Javanese ethnic restaurant. This research aims to find out how the owners of the restaurant present the authenticity of the flavor and culture through atmospherics elements and challenges they face in bringing the authenticity of the flavor and culture. This study refers to the previous researches published in both national and international journals. The conceptual literature used in this research is Kotler’s atmospherics concept. This study provides a conceptual contribution to the study of the introduction of communication science and to contribute the thought on how to convey the authenticity of Javanese flavor and culture, considering that the authenticity cannot be determine objectively, but depends on the social construction. This study used Constructivist Paradigm. This research is a descriptive study with qualitative approach using phenomenology method. Subjects of this research were owners of Javanese ethnic restaurant in South Jakarta and Central Jakarta. Purposive sampling technique was used to select the informants using the snowball method. The validity of the study used a standard of credibility with its own specifications. Presenting the authenticity of Javanese ethnic flavor and culture was not an easy task. The restaurant owners could present through the elements of atmospherics emphasizing the ability of the senses of visual, aural, olfactory, and tactile that captured the stimuli in both the interior and exterior of the restaurant, music, scent of the fragrance of flowers and food, as well as room temperature. In addition to the elements, the owners specially brought and used certain ingredients, such as soy, rice, tofu, crackers, and tea, to keep the authenticity of the taste of Javanese cuisine. They believe that the water and soil texture in Java produce different flavors in those materials.